Analyzing High-Risk Fertility Behavior for Sustainable Maternal-Child Health: A 2017 Sociodemographic Study in Urban and Rural Indonesia - Utami, Asti Annisa; Murti, Fadhaa Aditya Kautsar; Yuniar, Popy; Herdayati, Milla (UI Scholars Hub, 2025)
Indonesia's goal of achieving Indonesia Emas 2045 hinges on improving Maternal-Child Health (MCH), essential for building a healthy and competitive population. Despite some advancements, the Maternal Mortality Rate (MMR) and Under-five Mortality Rate (U5MR) remain high, particularly because of High-Risk Fertility Behavior (HRFB). The HRFB poses significant risks to MCH, affecting both urban and rural women. This study aimed to identify the factors associated with HRFB in these areas to enhance MCH outcomes and support Indonesia's sustainable health goals. This cross-sectional study used a secondary dataset from the 2017 Indonesian Demographic Health Survey. A total of 20,530 women of reproductive age were included in this analysis. The main dependent variable was the HRFB, and the independent variables were split into three factors: individuals, households, and community factors. The overall prevalence of HRFB was 37.0%, with a slightly higher prevalence in urban areas (37.6%) than in rural areas (36.1%). In rural areas, HRFB was significantly associated with the wealth quintile, while in urban areas, it was linked to women's autonomy and education level. Addressing these factors is critical for improving MCH outcomes and reducing HRFB use.